Power in International Relations: Insights from Realist and Liberal Theories - Rawa M. Mahmood (European Scientific Journal, ESJ, 2025)
The concept or factor of power has been given great importance in the social sciences in general and in the fields of political science and international relations in particular. However, the concept of power is a vague and controversial concept and has been defined in various ways, despite being mixed with other concepts and terms such as authority, purpose, ability, oppression, influence and other concepts close to the meaning of power. Due to its significance, the concept of power has been explored through numerous studies and theories since ancient times. Above all, both realism and liberalism have interpreted the concept of power and its importance in the international arena. Realism and its thinkers emphasize military strength and strategic alliances for the survival and hegemony of the state, while liberalism and its thinkers emphasize economic dependence, institutional cooperation and adherence to international norms and values ​​in order to achieve state security and influence. Based on the perspectives of the two major schools of international relations and political science, this study aims to interpret the concept and types of power in international relations. Simultaneously, it compares the perspectives of both schools and their thinkers and theorists on the concept of power and its significance in international politics.